Effects of dietary seaweed on sow and progeny performance and evaluation of an algae-clay complex-based feed additive and diet formulation on finishing pig growth performance - Del Tuffo, Leandro (Kansas State University, 2019)
This thesis involved utilizing dietary feed additives in swine rations. Chapter 1 is a literature review of the need for added vitamins in growing and finishing rations for swine. Chapter 2 evaluated the effects of a dietary seaweed on 28 sows from day 30 of gestation until weaning and progeny from birth until market. Maternal Oceanfeed Swine supplementation did not improve (P > 0.10) sow or litter performance. No differences were observed in colostrum yield, or colostrum and milk composition between the two treatments. In the nursery period, there was no evidence (P > 0.10) for main effect or sow by nursery treatment interactions. There was no evidence for fecal score differences between treatments on d 0, 7 and 21 after weaning. On day 56 after weaning, there was an increased proportion of pigs with the families Peptostreptococcaceae and Veillonellaceae in those fed Oceanfeed Swine in the nursery and originating from Oceanfeed Swine-fed sows. Pigs from this treatment combination also had increased mean number of species detected within the families Ruminococcaceae and Lachnospiraceae and had lower mean number of species detected within the family Fusobacteriacea. In the finishing period, no evidence for main effects or interactions (P > 0.10) were observed on overall growth performance. Chapter 3 evaluated the effects of an algae-clay-complex-based (ACC) feed additive and diet formulation (High or Low diet energy and amino acids) regimen on growth performance and carcass characteristics of finishing pigs. Overall, ADG was greater (P = 0.027) for pigs fed added ACC diets compared with those fed diets without ACC. This was a result of late finishing (d 56 to 90) increases (P < 0.019) in ADG and G:F for ACC fed pigs compared with those fed no ACC. Overall, pigs fed High diets had improved growth performance and heavier live weighs than pigs fed Low diets. For carcass characteristics, pigs fed High diets tended to have greater (P = 0.067) loin depth and greater (P < 0.001) carcass weight than pigs fed Low diets. No evidence for differences was observed for carcass characteristics between the control and added ACC fed pigs.
Keywords: Swine nutrition; Growth performance; Seaweeds; Microbiota; Algae-clay complex